Alih Kode dan Campur Kode Guru-Guru Bahasa Arab Pada Grup Whatsapp Majma’ Al-Lughah Al-‘Arabiyyah - Fauzan, Ahyar; Nasrullah, Ahmad; Hidayat, Tatang (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2022)
Objective: This study aims to mention examples of code switching or code mixing for Arabic teachers in the Majma' Al-Lughah Al-'Arabiyyah Whatsapp group, explain the meaning of code switching or code mixing used, and mention the factors that encourage the use of code switching and code mixing. Design/Methodology: This study uses a qualitative approach and a descriptive method. The researcher collected chat data from the Majma' Al-Lughah Al-Arabiyyah WhatsApp group related to code switching and code mixing, then performed data classification, analysis, and conclusion. Findings: Researchers found 22 code mixing, and 6 code switching. While the factors that cause the use of code mixing and code switching are seven, namely: (1) Arabic speaking habits, (2) speakers do not master Indonesian, (3) limited meaning, (4) as a form of respect, (5) use of more popular terms, (6) enhance a sense of humor, and (7) speech situations. The most dominant factor is the speaker's habit of speaking Arabic and the speaker is not fluent in Indonesian, and the least dominant factor is the factor of increasing prestige. Research Limitations/Implications: This research is limited to Arabic teachers at the Majma' Lughah Al-Arabiyyah institution, with a span of only two months. Even so, this research has been able to provide an overview of the use of code switching and code mixing in the Majma' Al-Lughah Al-Arabiyyah WhatsApp group as a whole.